Effect of dietary fish meal replacement with spray dried chicken plasma on growth, feed utilization and antioxidant capacity of largemouth bass (Micropterus salmoides) - Jianming Xu; Zhengyu Sheng; Naisong Chen; Ruitao Xie; Haitao Zhang; Songlin Li (Aquaculture Reports, 2022)
The present study was aimed to explore the influence of graded replacing fish meal (0.00%, 14.29%, 28.57%, 42.86%, and 57.14%) with spray dried chicken plasma (SDCP) on growth performance, feed utilization, and antioxidant capacity of largemouth bass. Triplicate groups of fish (initial weight: 10.05 ± 0.05 g) were fed experimental diets twice daily for 8 weeks. Results indicated that specific growth rate and feed intake of fish were not remarkably influenced with the replacement of fish meal. Meanwhile, no significant difference was observed in feed intake and feed efficiency ratio among treatments. The inclusion of SDCP significantly elevated crude protein content of muscle, liver and whole fish body, which resulted in the increased protein retention rate. Meanwhile, the lipid retention rate was also significantly increased with the replacement of fish meal. The replacement of 57.14% fish meal with SDCP significantly reduced the content of lipid peroxidation product malondialdehyde. Meanwhile, the total antioxidant capacity and catalase activity was significantly higher in fish fed the diet with replacement of 57.14% fish meal compared to the control group. In above, 57.14% fish meal could be substituted by SDCP in diets for largemouth bass under this experimental condition.